The hobbit, or, There and back again - Tolkien, J. R. R. (John Ronald Reuel), 1892-1973; Catlin, Jemima (Boston : Houghton Mifflin Harcourt, 2013)
Bilbo Baggins, a respectable, well-to-do hobbit, lives comfortably in his hobbit-hole until the day the wandering wizard Gandalf chooses him to take part in an adventure from which he may never return.
An unexpected party -- Roast mutton -- A short rest -- Over hill and under hill -- Riddles in the dark -- Out of the frying-pan into the fire -- Queer lodgings -- Flies and spiders -- Barrels out of bond -- A warm welcome -- On the doorstep -- Inside information -- Not at home -- Fire and water -- The gathering of the clouds -- A thief in the night -- The clouds burst -- The return journey -- The last stage.
Keywords: Baggins, Bilbo -- Fiction; Hobbits (Fictitious characters) -- Fiction; Dwarfs (Folklore) -- Fiction; Middle Earth (Imaginary place) -- Fiction; Gandalf (Fictitious character) -- Fiction; Gollum (Fictitious character) -- Fiction; Quests (Expeditions) -- Fiction; Rings -- Fiction; Wizards -- Fiction; Dragons -- Fiction; Good and evil -- Fiction; Treasure troves -- Fiction; Voyages and travels -- Fiction; Fantasy; Terre du Milieu (Lieu imaginaire) -- Romans, nouvelles, etc; Hobbits (Personnages fictifs) -- Romans, nouvelles, etc; Nains (Folklore) -- Romans, nouvelles, etc; Gollum (Personnage fictif) -- Romans, nouvelles, etc; Romans, nouvelles, etc; Dragons -- Romans, nouvelles, etc; Recherche -- Romans, nouvelles, etc; Voyages -- Romans, nouvelles, etc; FICTION / Fantasy / Epic; FICTION / Fantasy / Action & Adventure; FICTION / Fantasy / Dragons & Mythical Creatures; Fantasy fiction, English; Middle Earth (Imaginary place); Fantasy fiction; Hobbits (Fictional characters) -- Fiction; Baggins, Bilbo (Fictional character) -- Fiction; Middle Earth (Imaginary place) -- Fiction; Young adult fiction; novels; Novels; Fantasy fiction; Fiction; Fantasy fiction; Fantasy fiction; Novels; Fiction; Romans; Fantasy fiction